The efficacy of the interventional health education program for oral health improvement in school children - Lalić Maja; Aleksić Ema; Gajić Mihajlo; Milić Jasmina; Malešević Đoka (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. Dental caries and gingivitis are common in school children although they can be prevented through the health education and application of preventive measures. The aim of this study was to determine the prevalence of caries, gingivitis and orthodontic irregularities in school children and to assess the efficacy of health education program in relation to the plaque and gingivitis control as well as caries treatment. Material and Methods. This study included 56 second grade students with early mixed dentition and 56 seventh grade students with permanent dentition, from elementary school "Borislav Petrov Braca" in Pancevo. DMFT/dmft index, Plaque index (PI) according to Sillness-Löe, and the prevalence of gingivitis and orthodontic anomalies were determined by clinical examination. The Interventional Program included oral hygiene education and the application of prophylactic measures. At one and six months follow-ups, PI, gingival health and changes in DMFT/dmft structure were reexamined. Results. Gingivitis was recorded in 78.56% of II and 50% of VII grade students. In the II grade students, mean DMFT was 1.36±1.41, and dmft 5.07±2.66. In the VII grade students mean DMFT was 4.36±3.34. The most common orthodontic anomalies were narrow maxilla, deep bite and distal bite. After six months of conducting the Program, reduction of gingivitis and number of carious teeth in DMFT/dmft structure as well as oral hygiene improvement were achieved in both age groups. Conclusion. Oral hygiene, dental status and the prevalence of orthodontic anomalies in school children indicate the necessity to intensify preventive measures. Health education programs contribute to improvement of oral health and increase motivation for self-care in children.